The Effect of Using Technological Innovations on the Achievement of Seventh-Grade Female Students in the Subject of Mathematics (The International Journal for Scientific Research, 2024)
The study aimed to determine the effect of using technological innovations on the achievement of seventh-grade female students in the subject of mathematics. To know this effect, the descriptive analytical method was used, which is based on collecting data from sample members and then analyzing and interpreting the data. Two research tools were used: tests of reliability and validity and a questionnaire to measure the impact of using technical innovations in teaching mathematics. The study included all female students in the second intermediate grade at the Umm Habiba Complex for Al-Quran Al-Karim Memorization in Riyadh. It was conducted during the third semester of the year 2024. There were forty-six female students. The sample individuals were chosen by a simple random method.The results of the study showed the effectiveness of using technical innovations in raising the achievement level at the level of understanding, remembering, and application among the research group. It also became clear that the use of modern technologies increases the efficiency of students' comprehension and increases their achievement abilities. It showed that 70% of the students' understanding of mathematics depends on using modern.Methods for teaching mathematics subjects considering these results, the researchers presented some proposals for employing technical innovations to teach and learn mathematics. Researchers also proposed suggestions for conducting some future studies to reveal the impact of employing technical. Innovations on some variables related to teaching and learning mathematics.
Keywords: Technical Innovations; Educational Techniques; Academic Achievement; Second Intermediate Grade; Mathematics